Application of orthogonal metal–ligand interactions for the synthesis of interpenetrating metallopolymer networks featuring shape-memory and self-healing abilities. Issue 47 (3rd November 2022) - Meurer, Josefine; Bätz, Thomas; Hniopek, Julian; Bernt, Carolin; Zechel, Stefan; Schmitt, Michael; Popp, Jürgen; Hager, Martin D.; Schubert, Ulrich S.
Abstract : This study presents interpenetrating metallopolymer networks (IPNs) based on the orthogonality of two different metal complexes. The synthesized IPNs exhibit excellent shape-memory and self-healing abilities. Abstract : This study presents the simplified synthetic procedure of rewritable shape-memory metallopolymers, additionally featuring self-healing abilities. The formation of different orthogonal metal-complexes is applied to prepare interpenetrating metallopolymer networks (IPNs). Two different linear polymers, one bearing terpyridine and the other containing trt-histidine ligands in the side chains, are individually synthesized via a controlled radical polymerization procedure. After the simple mixing of both polymers, metal salt(s) are added inducing the formation of stable terpyridine and labile trt-histidine metal complexes simultaneously, whereby an interpenetrating metallopolymer structure is generated. FT-Raman spectroscopy is applied to confirm the successful formation of the desired complexes. The resulting IPNs are investigated in a detailed fashion via differential scanning calorimetry as well as thermogravimetric analyses. Furthermore, thermo-mechanical analysis revealed excellent shape-memory abilities with strain fixity and recovery rates up to 99%. Moreover, as part of this kind of investigation, the rewriting of the permanent shape and its influence on the shape-memory abilities is studied, revealing the possibility to program and determine a completely new permanent shape without reducing the shape-memory abilities in a significant manner. Additionally, self-healing abilities are observed and scratch-healing efficiencies up to 98% could be reached.